The role of social media during the 2015 voting process in the Nigeria election - Temitope, Olanrewaju Abdus Samad; Ahmad, Rahayu (MAXWELL Science Publication, 2017)
The rise in the use of social media in recent years had altered the landscape of events such as elections, disasters and political uprisings through its ability to serve as a source of information, recruitment and mobilization. These changes lead to the need to study the use of social media on how it influenced the Nigeria 2015 elections. Social Network Analysis (SNA) was used on the network structure generated during the election. This enabled the identification of influencers, the spread of influence and the way the media was used. As complimentary analysis, content analysis was performed on tweets submitted during the election process. The findings demonstrate how social media is used as an avenue for encouraging people to vote, collation and preservation of the election results which prevents election manipulation that usually happens in Nigeria. Furthermore, this study grounded on two-step flow theory shows influence propagation occurred primarily from the media houses and few citizens to the entire populace. Additionally, this study shows the use of social media in election monitoring and equally pave way for future research.